Reducing Racial Inequality in Access to the Ballot Reduces Racial Inequality in Children's Later-Life Outcomes - Daniel Jones; Ying Shi (Institute of Labor Economics (IZA), 2022)
The Voting Rights Act (VRA) of 1965 removed barriers to voting for Black Americans in the South; existing work documents that this in turn led to shifts in the distribution of public funding towards areas with a higher share of Black residents and also reduced Black-White earnings disparities. We consider how expanded access to the ballot improved the well-being of children, and in doing so document that the immediate effects of expanded voting access last well into the next generation. Specifically, within a cohort-based differences-in-differences design, we test how early-life exposure to the VRA differentially impacted later-life outcomes of Black Americans. We find that increased exposure to the VRA before the age 18 leads to higher educational attainment and earnings in adulthood for Black Americans, with little or no impact on whites.
Keywords: J15; N12; D72; 330; Voting Rights Act; racial inequality; voting; childhood exposure